Kapasitas Memori Kerja (KMK) dalam Pemecahan Masalah Matematika - Deka Anjariyah; Dwi Juniati; Tatag Yuli Eko Siswono (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2020)
This literature study research examined relevant theories about KMK and problem solving to discuss how KMK could help people when trying to solve problems, especially mathematical problems. Methods of data collection through literature study. The data obtained was compiled, analyzed in depth and concluded. The results showed that KMK played a role in maintaining and retrieving information in LTM. KMK could impact on successful problem solving namely supporting more effective problem solving by activating the retrieval and using of relevant information to the domain. KMK helped narrow the search space for appropriate solutions and could help problem solvers focused on problems and experiences that were lacking in the interruption of irrelevant information. KMK resources contributed to the development of domain related knowledge